Resilience processes, engagement and emotional competencies, in professionals attending elder people in violence situations in Saltillo, Coahuila and Monterrey, Nuevo León, Mexico = Procesos de resiliencia, engagement y competencias emocionales en profesionales de atención a población adulta mayor en situaciones de violencia en Saltillo, Coahuila y Monterrey, Nuevo León México - Castro Saucedo, Laura Karina; León Alvarado, César Arnulfo de; Acevedo Alemán, Jesús; Ramírez Ríos, Cesar Omar (2018)
In recent years, an increasing number of studies have investigated resilience, which is considered a phylogenetic process developed to increase survival (Stein, 2009; Aparecida dos Santos & Nunes Moreira, 2014). Resilience is a construct that has been the topic of many studies. The objective of this investigation is to identify the relationship between the five dimensions of resilience in professionals who tend to elderly people, labor engagement and the emotional competencies. Several linear regression models were used to investigate the levels of prediction between the independent and dependent variables. The main results show relationships among resilience and its different dimensions, engagement (β = .207; p = .005) and emotional competencies (β =.710; p =.001) including four of its five dimensions on the analysis (R2= .724, F = 108.63, gl = 2, p= .001).
En los últimos años se han incrementado los estudios sobre la resiliencia como un proceso desarrollado filogenéticamente para la supervivencia (Stein, 2009; Aparecida dos Santos & Nunes Moreira, 2014). El objetivo de esta investigación fue identificar la relación existente entre las dimensiones de la resiliencia de profesionales que atienden adultos mayores y el engagement laboral y la relación con las competencias emocionales. Se elaboraron modelos de regresión lineal para establecer los niveles de predicción entre las variables independientes y dependiente. Los principales resultados arrojan una relación entre la resiliencia (así como sus diversas dimensiones), el engagement(β = .207; p =. 005) y las competencias emocionales (β =.710; p =.001) incluyendo cuatro de las cinco dimensiones en el análisis (R2= .724, F = 108.63, gl = 2, p = .001).
En Revista Actualidades en Psicología, Vol. 32, no. 125 (julio - diciembre 2018)
Descripción basada en el contenido visto el 29 de junio 2023.
Keywords: RESILIENCIA (PSICOLOGIA); CUIDADORES -- PSICOLOGIA; INTELIGENCIA EMOCIONAL; COMPROMISO ORGANIZACIONAL; PSICOLOGIA DEL TRABAJO; ANCIANOS -- INVESTIGACIONES